Variability on morphological characters associated with pod shattering resistance in soybean - AYDA KRISNAWATI; M. MUCHLISH ADIE (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Krisnawati A, Adie MM. 2016. Variability on morphological characters associated with pod shattering resistance in soybean. Biodiversitas 17: 73-77. Pod shattering is one of the major constraint associated with soybean production during dry season in Indonesia. The objectives of the study were to investigate varietal difference of pod shattering and to identify the morphological pod characters related to pod shattering. The field study was carried out in Blitar (East Java, Indonesia) during the dry season 2015. Morphological traits of pod were studied for their association with pod shattering trait in 30 soybean genotypes. The results showed significant differences between genotypes for all characters studied. The degree of shattering varied among genotypes with shattering percentage ranging from 2.5% (G511H/Argom//Argom-2-1) to 100% (Grobogan) with mean of 30%.However, among the 30 genotypes studied, 13 genotypes were relatively resistant, 11 genotypes moderate, 1 genotype susceptible, and 5 genotypes were very highly susceptible. Further path coefficient analysis indicated direct effects of the pod wall thickness and pod length on shattering percentage while other causal effects were small. These characters (pod wall thickness and pod length) may play role as determinant factors in pod shattering resistance. Therefore, soybean resistance to pod shattering could be enhanced by increasing thickness of the pod wall. Keywords: Glycine max, pod characteristics, pod shattering, resistance